The use of social media and its impact on business growth / Muhammad Aqlan Mohamad Rosli and Nurwahida Fariza Wasilah - Mohamad Rosli, Muhammad Aqlan; Wasilah, Nurwahida Fariza (2022)
The purpose of this research project is to study on the relationship of The Use of Social Media and Its Impact Towards Business Growth and this study focusing on business owner in Klang Valley area. This study going on from 6th October 2021 until 31st August 2022. For this study, the researcher use questionnaire in collecting the data from the respondents. The results gain from this study has revealed three important findings which is the first findings where the majority of respondent has agreed that social media usage has increase the level of sales. The second findings which is the best social media to use for business and the third findings is the impact social media towards the sales growth. The conclusion that can be made from this finding is there is relationship between the use of social media and the impact towards business growth.